Trans Masculine Identities: Making Meaning in Gender and Transition - (:unkn) unknown (My University, 2018)
Perspectives on transgender identity have evolved through time, and various models of transgender identity development are emerging from multiple fields of study. However, little is known about what gender identity means to self-identified trans masculine individuals. Additionally, across existing transgender identity development stage models, the concept of transition is often assumed to include some form of medical intervention, with the acquisition of such interventions playing a key role in one’s developmental trajectory. Furthermore, current literature often implies transition is an end goal in the path toward integrating one’s core identity. However, there is little to no research exploring how trans masculine individuals experience or make meaning of their gender identity or transition in one’s developmental trajectory. This dissertation is an exploratory effort designed to highlight and honor the experiences of young adults who identify as trans masculine, and the meanings they make in gender and transition. This work contributes toward building a strong foundation from which theoretical frameworks relevant to trans masculine individuals can emerge. Added benefits of this research include opportunities for shaping policy and best practices in affirmatively meeting the health care needs of trans masculine individuals. To this end, qualitative methodology guided by Interpretive Phenomenological Analysis (IPA) was employed. Discussion includes analysis through the lenses of interpretivism, poststructuralism and critical theory, as the underlying aim of each lens is to understand, deconstruct and emancipate, respectively. With IPA as a guiding methodology, participant responses converged around nine superordinate themes: (1) Awareness of Self in Context, (2) Safety, (3) Impact of the Binary, (4) Visibility, (5) Create Space for Trans Masculine Identity, (6) Transition is Dynamic, (7) Resilience, (8) Generational Change, and (9) Perspectives on Health Care.
Keywords: identity development; qualitative; transgender; trans health; trans masculine